Practices and stability of working capital investment and financing policies: evidence from Malaysia public listed companies / Mohamad Shahril Ishak, Noryati Ahmad and Fahmi Abdul Rahim - Ishak, Mohamad Shahril; Ahmad, Noryati; Abdul Rahim, Fahmi (Research Management Centre (RMC), 2020)
Working capital management is related to the operating activities of a company and therefore is one of the most significant decisions that managers need to make. Despite the important function of working capital management, this area has been very scantily researched. Aggressive or conservative working capital investment and financing policies imply the liquidity position of the company that could affect its operating profit. Not much is known about the working capital management practices among Malaysian companies. Hence, this study takes the task of investigating the trend and practices of working capital management policies of the Malaysian public listed in seven industry sectors. The industry sectors involved are industrial products, trading and services, consumer, properties, construction, plantation and technology. A total of 573 companies are involved in covering the period from 2001 until 2017. Using one-way ANOVA analysis, mean difference t-test and rank correlation test several findings were discovered. The practices of working capital investment policy (WCIP) for most industry sectors are consistently being applied throughout the study period instead of implementing the working capital financing policy (WCFP). Furthermore, the industry means ratio differences of WCIP and WCFP are statistically significant in most industry sectors studied even though the results of WCFP are mostly negative. This connotes a distinct difference in the asset management and financing policies between industry sectors. Lastly, the insignificant statistically negative results of the rank coefficient of correlation test provides inconclusive evidence if the conservative (aggressive) WCIP pursued is accompanied by the aggressive (conservative) WCFP.